Penggunaan Aplikasi Kalkulator Mawarits dalam Pembagian Harta Warisan - Fauzah, Wida Nur; Pahlevi, M. Firza; Gautama, Zaki; Syamsiah, Syamsiah; Armansyah, Yudi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
According to Islamic law or the science of faraidh, the distribution of inheritance is one of the important aspects that has strict rules. Since the calculation of the inheritance share for each heir varies depending on their status and relationship, this process often leads to problems for some members of society. Injustice, and even family conflicts, can arise from mistakes in calculating the inheritance shares. Various applications have been developed in today's digital era to facilitate the calculation of inheritance in accordance with Islamic law. One of them is the inheritance calculator. The aim of this research is to examine how effective and easy it is to use the inheritance calculator in assisting the process of dividing inheritance based on Islamic law. The results of the research show that the inheritance calculator application is very helpful in calculating the inheritance shares quickly and accurately, using case studies involving users of the application. This application can help the general public better understand the science of inheritance and reduce errors in manual calculations. Additionally, since it complies with Islamic law, this application enhances time efficiency and provides a sense of justice. Thus, the inheritance calculator application can be used to address issues related to the distribution of inheritance in a practical and educational way. Moreover, it can also function as a medium for da'wah that brings society closer to fair and systematic Islamic law.